Characterization of a chimeric chemokine as a specific ligand for ACKR3. Issue 2 (30th March 2018) - Ameti, Rafet; Melgrati, Serena; Radice, Egle; Cameroni, Elisabetta; Hub, Elin; Thelen, Sylvia; Rot, Antal; Thelen, Marcus
Abstract: Chemokines, small chemotactic cytokines, orchestrate cell migration by binding to their cognate chemokine receptors. While chemokine-mediated stimulation of typical G-protein-coupled chemokine receptors leads to cell migration, binding of chemokines to atypical chemokine receptors (ACKRs) does not induce canonical signaling. ACKRs are considered important chemokine scavengers, that can create gradients which help direct cells to sites of inflammation or to their immunological niches. Synthetic chemokines have been used in the past to study and decode chemokine-receptor interactions. Characterizing specific chemokine-ACKRs interactions is challenging because the chemokines bind multiple receptors; for example, the ACKR3 ligands CXCL12 and CXCL11 bind to the canonical receptors CXCR4 and CXCR3, respectively. Here, we present the engineering of a chemokine-like chimera, which selectively binds to ACKR3. The addition of a ybbR13 tag at the C-terminus allows site specific enzymatic labeling with a plethora of fluorescent dyes. The chimera is composed of the N-terminus of CXCL11 and the main body and C-terminus of CXCL12 and selectively interacts with ACKR3 with high affinity, while not interfering with binding of CXCL11 and CXCL12 to their cognate receptors. We further provide evidence that the chimera can be used to study ACKR3 function in vivo. The chimeric chemokine CXCL11_12 is a selective high affinity ligand for the typical chemokine receptor ACKR3.